Production and characterization of biodiesel from tamarind seed oil - Hanif, Muhammad Asif; Mushtaq, Ayesha; Zubair, Muhammad; Rashid, Umer (2018)
Biodiesel production from food graded oils is not economical due to high prices. Almost 80-85% cost of biodiesel is due to feedstocks. And currently used non-edible, waste oils are not capable of large scale biodiesel production. Therefore, search for other non-edible oil bearing feedstocks is need to be continued. The present investigation is an attempt to use non-edible tamarind seed oil as an inexpensive, sustainable and potential feedstock for biodiesel synthesis. Tamarind seed oil was converted to biodiesel by acid (HCl), base (KOH) and enzyme (immobilized lipase) catalysed transesterification. Tamarind seed biodiesel was found to have low iodine value (26-32) and high cetane number (65-68). Pour point values of biodiesel were ranged from -0.3 to -4.2. The components of produced biodiesel were evaluated by gas chromatographic-mass spectroscopic analysis.